PENGGUNAAN MEDIA FLANNEL BOARD DALAM MENGEMBANGKAN KEMAMPUAN MENGENAL HURUF PADA ANAK - Titin Kusayang; Mhd. Rasidin; Winda Oktaviana (Jurnal Muara Pendidikan, 2023)
This research aims to determine the development of the ability to recognize letters in RA. At-Taqwa Kumun. This classroom action research uses the Kemmis and Mc Taggart model which includes four stages, namely planning, action, observation and reflection. The population in this study were 13 children in RA At-Taqwa Kumun group B aged 5-6 years. The data collection techniques for this research are observation, interviews and documentation. The results of the research show that using flannel board media can improve children's ability to recognize letters in RA. At-Taqwa Kumun, Sungai Penuh City. This can be seen from the results of the pre-cycle, cycle 1 and cycle 2 which experienced an increase. The score obtained by pre-cycle children was 47.5%. In cycle 1 the score obtained by the child was 59.72%. In cycle 2 the score obtained by the child was 66.53%.